(untitled) (Homoeopathy for All, 2026)
Ankylosing spondylosis (AS) is a chronic inflammatory rheumatic dis order primarily affecting the axial skeleton, causing progressive stiff ness, postural deformity, and restrict ed mobility. It is closely associated with HLA-B27 positivity, signifying a strong autoimmune component. Conventional management relies on NSAIDs, corticosteroids, and biolog ics, which may provide temporary relief but often lead to adverse effects such as gastric irritation and steroid dependency.